B‐cell maturation antigen‐specific chimeric antigen receptor T cells for multiple myeloma: Clinical experience and future perspectives. Issue 8 (30th April 2020) - Sellner, Leopold; Fan, Fuli; Giesen, Nicola; Schubert, Maria‐Luisa; Goldschmidt, Hartmut; Müller‐Tidow, Carsten; Dreger, Peter; Raab, Marc S.; Schmitt, Michael
Abstract: Despite major advances in the treatment of multiple myeloma (MM), it remains a largely incurable disease with long‐term control often dependent on continuous therapy. More effective, better tolerated treatments are therefore required to achieve durable remissions and to improve the quality of life of MM patients. Adoptive immunotherapy employing T cells expressing chimeric antigen receptors (CAR) is currently among the most promising treatment approaches in cancer. Within the target portfolio for MM immunotherapy, B‐cell maturation antigen (BCMA) is among the most widely studied target antigens. BCMA is consistently expressed on MM cells and, importantly, is not expressed in critical healthy tissue. For this reason, it is an ideal target for MM immunotherapy. Several clinical trials evaluating different BCMA‐targeting CAR constructs have been initiated and early results are very promising. However, in this rapidly developing clinical landscape, the ultimate role of BCMA‐specific CAR‐T cell therapy remains unclear. In this review, we will summarize currently available clinical data on BCMA‐directed CAR‐T cells and discuss potential future perspective for this promising treatment approach in MM.